Korelasi Keterampilan Interpersonal dengan Hasil Belajar Kimia Siswa pada Sistem Pembelajaran Tatap Muka Terbatas - Rusfamahira Rusfamahira; Andi Ifriani Harun; Rahmat Rasmawan; Erlina Erlina; Ira Lestari (Orbital: Jurnal Pendidikan Kimia, 2022)
When learning offline, the implementation of interpersonal skills-based learning has been widely carried out. Study on the effectiveness of implementing interpersonal skills in chemistry learning has also been shown to improve students’ chemistry learning outcomes. However, the transition of the learning system to blended learning has reduced the communication process between students and between teachers and students. Even interpersonal skills-based learning cannot be implemented. Therefore, this research aims to find out the correlation value between student interpersonal skills and their chemistry learning outcomes during the blended learning system. The research design is quantitative descriptive, with 101 students from class XI IPA as the research sample. The instruments used in the research were questionners and documentation studies. Data from questioners and documentation were analyzed by rank spearman/correlation test. Based on the correlation test between student interpersonal skills and chemistry learning outcomes, it was found that the correlation value is equal to 0,639. The correlation value which is equal to 0,639 indicates that correlation between interpersonal skills and chemistry learning outcomes have a strong and mutually influencing relationship. Thus, interpersonal skills can improve student chemistry learning outcomes. The contribution of interpersonal skills in improving students’ chemistry learning outcomes during the blended learning system is 40.83%